ANALISIS USAHA BERBASIS MIKRO KELOMPOK USAHA BERSAMA (KUBE) NURHIKMAH DI KABUPATEN BATU BARA - Fadli Akbar Lubis (Program Studi Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan Universitas Lambung Mangkurat, Banjarmasin, 2021)
This study aims to determine the feasibility level of the karas-karas industry at KUBE Nuhikmah in Batu Bara Regency. The research was conducted purposively with the consideration that this area is an area that has potential in the field of traditional culinary businesses and the majority of the population is of the Malay ethnicity, and there are craftsmen in the traditional karas-karas cake industry. From the results of the investment analysis using the Benefit / Cost (B / C) formula, the karas-karas industry of KUBE Nurhikmah in the research area is feasible to operate with a value of B / C> 1, that is 2.06> 1. From the switching value analysis, the calculation results of the maximum increase of production costs by 90% and a decrease in sales of 30% can still be tolerated in KUBE Nurhikmah's karas-karas industry business.